A New Cost Effective Approach to Suppress Very Fast Transients on Power Transformers Connected to Gas Insulated Substations - Babaeilaktarashani, Mehdi (Curtin University, 2016)
This thesis investigates the feasibility of a new method to prevent internal resonance in transformers connected to gas insulated substation due to very fast transient overvoltage in the GIS. The possibility of utilizing a cost effective RC surge suppressor to prevent internal transformer resonance is analyzed and the optimum suppressor in terms of capability to suppress high risk frequencies of VFTO is proposed. In comparison with other existing methods, the proposed method is a simple and cost effective method.